The Visa Liberalization and the Republic of Macedonia: Two Sides of the Coin - Vankovska, Biljana (My University, 2014)
The Schengen ‘wall’ that had kept the Western Balkans and the Republic of Macedonia cast out from the EU mainland was removed in 2009. Symbolically it coincided with St. Nicholas Day i.e. the celebration of the patron of children and travelers. The paper examines the effects of visa liberalization and the effects that may follow in case the newly adopted suspension mechanism is fully implemented. The basic assumption is that visa liberalization served as a ‘carrot’ to move forwards the EU integration process while the suspension mechanism is more of a disciplinary measure (the ‘stick’) but also an indication of a securitized migration policy. The paper underlines how visa liberalization has affected the governments’ treatment of the ‘bogus’ asylum seekers (mostly citizens of Roma and Albanian origin). The research question concerns the trade-off that national governments have made in order to preserve visa liberalization and the impact in terms of human rights and discriminatory policies.
Keywords: EU, free movement, visa liberalization, Macedonia, asylum seekers, human rights